2020
DOI: 10.1007/s00269-020-01118-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-chemistry of micas belonging to the yangzhumingite-fluorophlogopite and phlogopite-fluorophlogopite series from the Apuan Alps (northern Tuscany, Italy)

Abstract: The present work reports the crystal-chemical characterization of micas from the Monte Arsiccio and Buca della Vena mines (Apuan Alps, Italy) through electron microprobe analysis, single-crystal X-ray diffraction, and Raman spectroscopy. The sample from the Monte Arsiccio mine can be classified as an intermediate member of the yangzhumingite-fluorophlogopite series, with average crystal-chemical formula (K0.85Na0.01Ba0.09)Σ=0.95(Mg2.11Fe2+0.23Fe3+0.11Cr3+0.01Al0.20Ti0.04☐0.30)Σ=3.00(Si3.20Al0.80)Σ=4.00O10.00F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…7a). In fact, this is in accordance with the peak assignment by Tlili et al (1989) and Lacalamita et al (2020), attributing the peaks near 650 and 680 cm −1 to Si-O b -Al and Si-O b -Si bond vibrations, respectively. Our analysis revealed that both ω 680 and FWHM 680 are sensitive to M Ti content (see Fig.…”
Section: Raman Peak Assignment and Effect Of Chemistrysupporting
confidence: 90%
See 3 more Smart Citations
“…7a). In fact, this is in accordance with the peak assignment by Tlili et al (1989) and Lacalamita et al (2020), attributing the peaks near 650 and 680 cm −1 to Si-O b -Al and Si-O b -Si bond vibrations, respectively. Our analysis revealed that both ω 680 and FWHM 680 are sensitive to M Ti content (see Fig.…”
Section: Raman Peak Assignment and Effect Of Chemistrysupporting
confidence: 90%
“…Therefore, the dataset of sample B3 was not taken into consideration while constructing calibration curves. On the other hand, high total oxides equal to 100 wt % can be explained by high F content such as in fluorophlogopite (e.g., Gianfagna et al, 2007;Scordari et al, 2013;Lacalamita et al, 2020). The fraction of trivalent iron and its distribution over the M and T sites for samples B4, B13, B14, B17, B19, and B21 was derived from the Mössbauer spectra (see Table S2 and Fig.…”
Section: Chemical Composition From Wavelength-dispersive Empa and Mös...mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is a fluo-sulfate. Recently, Lacalamita et al [78] detected high F content in micas from the Monte Arsiccio mine; these phases may be the source not only of K and Al, but also for F. Krausite was observed as overgrowths on the other sulfates (i.e., römerite, coquimbite-Figure 17) and it has been found also on alunogen and halotrichite. Krausite seems to postdate the crystallization of alunogen, whose individuals are superficially corroded, whereas krausite crystals are shiny, without any hints of alteration.…”
Section: The Fornovolasco Minementioning
confidence: 97%